1996
DOI: 10.1055/s-0038-1650593
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen Activator Inhibitor 1 Is Elevated in the Children of Men with Premature Myocardial Infarction

Abstract: SummaryTo assess whether plasminogen activator inhibitor 1 (PAI-1) activity is elevated in the progeny of young coronary men, 193 young subjects were recruited and divided into two groups. Group A consisted of 104 children whose fathers had suffered a myocardial infarction before the age of 55 (“cases”). Eighty-nine young subjects matched for age, sex, body mass index (BMI) and smoking habits without familial history of coronary artery disease (CAD) served as controls (group B). Children with a family history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…However, this finding was based on univariate analysis alone and no correlation was found between PAI-1 and tPA. 40 In the present study, we have identified the well reported relationship between the 4G allele of the PAI-1 gene 4G/5G polymorphism and increased PAI-1 levels but found no difference in genotype frequency between relatives and controls. This is in contrast to a study by Margaglione et al 39 which found the 4G/4G genotype to be independently associated with family history of MI.…”
Section: Insulin Resistance Syndromesupporting
confidence: 43%
“…However, this finding was based on univariate analysis alone and no correlation was found between PAI-1 and tPA. 40 In the present study, we have identified the well reported relationship between the 4G allele of the PAI-1 gene 4G/5G polymorphism and increased PAI-1 levels but found no difference in genotype frequency between relatives and controls. This is in contrast to a study by Margaglione et al 39 which found the 4G/4G genotype to be independently associated with family history of MI.…”
Section: Insulin Resistance Syndromesupporting
confidence: 43%
“…Radilis et al [24] determined the activity of PAI-1 in children whose fathers had myocardial infarction before the age of 55 years. In both the children and their fathers, a significant increase in the activity of PAI-1 was found.…”
Section: Discussionmentioning
confidence: 99%
“…79 Plasminogen activator inhibitor 1 is elevated in the children of men with premature MI, and these elevated plasminogen activator inhibitor 1 levels impair fibrinolytic capacity. 80 Finally, the most recently described risk factor is C-reactive protein, which may act as a marker of "microinflammation," hypothesized to have a role in the initiation and progression of atherosclerosis. In the Physicians' Health Study, this risk factor increased MI and stroke risk almost 3-fold and was independent of lipid and nonlipid risk factors.…”
Section: Determining Optimal Threshold Levels Of Absolute Chd Risk Tomentioning
confidence: 99%